Evaluation of Shrinkage, Mass Changes and Fracture Properties of Fine-aggregate Cement-based Composites during Ageing. (2017) - Kucharczyková, Barbara; Šimonová, Hana; Keršner, Zbyněk; Daněk, Petr; Kocáb, Dalibor; Misák, Petr; Pőssl, Petr
Abstract: The paper deals with the experimental determination of relative length changes development during cement based composite ageing. Special moulds with the dimensions 100 × 60 × 1000 mm were used for the measurements. These moulds were filled and placed on an advanced weighing table that enables continuous recording of mass losses caused by free drying of the specimen surface. In this way, the mass losses and changes in the length of the cement composite in the moulds were measured simultaneously. The shrinkage moulds were modified in order to measure also the long-term relative deformation of fine-aggregate concrete specimens as a result of drying. The outputs of the measurement are given in the form of the diagrams displaying the relationship between the relative length changes or the mass losses and the time of cement composites ageing. Besides the measurement of length changes, three-point bending fracture tests at the age of 3 and 28 days were also performed. The modulus elasticity, effective fracture toughness and specific fracture energy values were determined from load versus deflection diagrams recorded during fracture experiments on the specimens with dimensions 40 × 40 × 160 mm.